The Development of Magic Disc Tajwid Media in Qur'an-Hadith Instruction to Enhance the Understanding of Fourth-Grade MI Students - Siti Lailatur Rohmah; Miftakhul Ilmi Suwignya P; Siti Asiah (Indonesian Journal of Teacher Education, 2026)
This study aimed to develop a valid, practical, and effective magic disc tajwid media to improve fourth-grade students’ understanding of the nun mati (nun sakinah) and tanwin rules in the Qur’an Hadith subject at MI Bustanul Ulum Brudu Sumobito, where learning had relied mainly on lecturing with limited practical tools. The study used the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) and a One-Group Pretest-Posttest design involving 18 fourth-grade students. Data were collected through interviews, observations, documentation, and questionnaires, then analyzed descriptively. Expert validation showed the media was highly feasible, with an average validity score of 96,67%. The media was also rated highly practical, with an average practicality score of 93.25% based on teacher (96.22%) and student (85.30%) responses. The Magic Disc Tajwid media is thus declared valid, practical, and effective for teaching the nun mati and tanwin tajwid material in Madrasah Ibtidaiyah.